FORUM NON CONVENIENS - Gonson, S. Donald (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 1999)
The United States forum non conveniens doctrine refers to the discretionary power of the court to decline jurisdiction when the convenience of the parties would be better served if the action was brought and tried in another forum. It is a flexible doctrine in that the ultimate resolution will depend of the particular facts of each case. The two-pronged United States forum non conveniens analysis places the burden of proof on the defendant to show the “availability” and “adequacy” of an alternate forum, and that the balance of relevant private and public interest factors favors dismissal. Such an analysis applied to the facts as found by the court in the Cambior decision reveals both the availability and adequacy of Guyana as an alternate forum. The available remedies to the plaintiff, although less extensive, would not be sufficient to find Guyana inadequate, nor would differences in procedural law between the two jurisdictions. Upon comparison with the Union Carbide case, it is apparent that private and public interest factors in Cambior are better served in Guyana. Thus, in light of Union Carbide, it seems that where Cambior first lodged in the United States, it would have been dismissed in favor of Guyana.